Understanding the hesitancy to disclose teen dating violence: Correlates of self-efficacy to deal with teen dating violence - Hébert Martine; van Camp Tinneke; Lavoie Francine; Blais Martin; Guerrier Mireille (Temida)
Dating violence (DV) is now recognized as an important public health issue. Prevention and intervention programs are being implemented in school contexts. Such initiatives aim to raise awareness among potential victims and offenders as well as among peer bystanders and offer adequate interventions following disclosure. Yet, a major challenge remains as teenagers may not disclose their victimization or may not feel self-efficient to deal with DV if they witness such violence. As such, teen DV remains largely hidden. A representative sample of 8194 students (age 14-18) in the province of Quebec, Canada was used to explore teenagers’ self-efficacy to reach out for help or to help others in a situation of DV victimization and perpetration. Analyses are conducted to identify possible correlates of self-efficacy in terms of socio-demographic variable (sex, age) and a history of child sexual abuse and dating victimization. Implications for prevention and support strategies are discussed.